2008
DOI: 10.1088/0953-8984/20/24/245102
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of hexatic and isotropic phases in two-dimensional Yukawa systems

Abstract: We performed Brownian dynamics simulations on the melting of two-dimensional colloidal crystals in which particles interact via a Yukawa potential. A stable hexatic phase was found in the Yukawa systems, but we also found that the melting of Yukawa systems is a two-stage melting, which is inconsistent with the Kosterlitz-Thouless-Halperin-Nelson-Young (KTHNY) theory. A two-phase coexistence region between the stable hexatic phase and the isotropic liquid phase was found. The behavior of point defects in the co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 36 publications
(54 reference statements)
4
26
0
Order By: Relevance
“…The intermediate hexatic phase was observed in many 2D systems including our NIPA monolayers [10], while the liquid-solid coexistence without a hexatic phase [43,44] and the hexaticliquid coexistence [45] were observed in other systems. In these coexistence states, or in the uniform hexatic phase, small defects are dispersed uniformly without condensing into large strips of liquid or lakes.…”
Section: D Meltingmentioning
confidence: 78%
“…The intermediate hexatic phase was observed in many 2D systems including our NIPA monolayers [10], while the liquid-solid coexistence without a hexatic phase [43,44] and the hexaticliquid coexistence [45] were observed in other systems. In these coexistence states, or in the uniform hexatic phase, small defects are dispersed uniformly without condensing into large strips of liquid or lakes.…”
Section: D Meltingmentioning
confidence: 78%
“…The setup is similar to the one reported in Refs. [27,28]. We consider a monoatomic system interacting through pairwise Yukawa potential [29].…”
Section: A Simulation Setupmentioning
confidence: 99%
“…We used a rectangular simulation box and applied periodic boundary condition on both directions. The ratio of the lengths of two sides is 2:√3 for the sake of minimizing box size effect [27,28,31]. All simulation runs were performed under canonical ensemble while the temperature control was achieved by Nose-Hoover thermostat.…”
Section: A Simulation Setupmentioning
confidence: 99%
“…Recently, the other melting scenario was proposed [24][25][26][27][28][29]. In contrast to the BKTHNY theory, it was shown that the system can melt through a continuous BKT type solid-hexatic transition, but the hexatic-liquid transition is of first-order [24][25][26].…”
Section: Introductionmentioning
confidence: 99%